A Building Students’ Life Skill through Project-Based Learning:: English - Nurhajati, Diani (Universitas Nusantara PGRI Kediri, 2019)
The academic goal of teaching in university level is to reach certain learning outcomes. Speaking for Informal Communication is one of the subjects which enable students to describe, explain, negotiate, persuade, and influence other speakers using the target language on certain topics. The lecturers not only have to choose an appropriate teaching strategy to reach the goal, but also to select the suitable materials and activities in order that the students can apply the skills of speaking. One of the strategies is by applying Project Based Learning in which the students must create a project in groups. Through this strategy the students are able to reach the academic goal of teaching speaking and practice to build some qualities in life skill, such as a) awareness of the students’ potency and the values found in the local wisdom, b) cooperative working and communication skill, c) critical thinking, d) academic skill, and e) honesty. Those qualities are very important to equip the students to win the global competition. This research describes how life skills were built through Project Based Learning in speaking class and the students’ perspective on how the qualities of life skills were built through the experience of creating project. It is a qualitative research which observed the process of teaching and learning in speaking class. Besides, in-depth interview to the students was carried out to collect the data on their perspective of those skills. The results show that through the stages of creating the project, that was vlog, the students felt that they got many challenges to create the project. They admitted that the challenges built their life skills.